Factors Affecting Hospital Business Continuity in Indonesia During the COVID-19 Pandemic: a Scoping Review - Tri Sumarni, Sandry; Chalik Sjaaf, Amal (Journal of World Science, 2022)
Introduction: The COVID-19 pandemic has created various challenges and problems for healthcare facilities around the world. This problem also occurs in Indonesia, a country with a high rate of transmission and death of COVID-19. Hospitals, both as health facilities and businesses, must determine the necessary strategies to ensure their business continuity during the Pandemic. Therefore, the factors that affect the continuity of the hospital's business must be determined before making a strategy. The purpose of this study was to identify and analyze the factors affecting the continuity of a hospital's business during a pandemic. Method: A scoping review was done using PRISMA-ScR guidelines and population, concept, context (PCC) framework. Studies from Pubmed, Google Scholar, and Portal Garuda were collected and analyzed. Results: Among 326 articles found, five studies were included and analyzed. Each study examined the impact of COVID-19 on various aspects of the hospital, both as a business and as a healthcare facility. Moreover, some studies also proposed solutions to minimize the impact of disruptions due to COVID-19. Changes and innovations in facing biological, financial, and resource management problems are essential for hospitals in Indonesia to maintain business continuity during the COVID-19 Pandemic. Conclusions: COVID-19 Pandemic brought significant challenges for hospitals around the world. Factors affecting hospital business continuation in Indonesia appear in biological, financial, and resource management problems.